Accident causation model for building construction sites - Asan, Amran (2017)
Construction safety at Malaysian building and construction project sites is of utmost importance due to the nature of the construction industry. Workplace safety is a care consideration for all types of organizations or stakeholders. However, statistics shows that safety at project sites is not adequately considered. Reports on site accidents represented nearly 50% of overall fatality cases across all industries. These statistics are indications of a continuing severity of building site accidents compared to others. Malaysian building site accidents are the results of various factors which are crucial to be identified. Therefore, a comprehensive understanding of the factors or the root causes that contribute to site accidents is essential. Thus, the aim of this study was to develop an accident causation model (ACM) at building construction projects sites, focusing on determining the significant factors that cause site accidents. These factors consisted of 93 items and they were divided into seven constructs. The study was undertaken in two stages. Firstly, relevant literatures were reviewed to identify the factors. The data were gathered to assess the suitability of the factors based on experts’ judgement and survey. Data obtained were statistically analyzed using the statistical tools in the Statistical Package for Science Social (SPSS) 20.0 and the proposed model was recognized. Then, data collected from actual survey involving 420 respondents were analyzed to test the research model validity and the proposed hypothesis using the Partial Least Squares - Structural Equation Model (PLS-SEM) tool. From the results, it was revealed that the seven constructs have a direct positive effect on accident causation. The developed model is fit (R2 value) and the identification of the seven constructs are significant (t-value). The model indicates that the highest impact on construction site accidents with a path coefficient β (beta) value is unsafe equipment, followed by job site conditions, natural disaster, unique nature of the industry, unsafe methods, organization and management, and human elements. In conclusion, the findings through the ACM model of this study are reliable and very useful for construction organizations or stakeholders understand the significant root cause of the project site accidents. Hence, this can assist them to further implement an appropriate control measures to prevent accidents in Malaysian building construction site projects.